Food hygiene and toxicology in ready to eat foods - Kotzekidou, Parthena (Academic Press is an imprint of Elsevier, 2016)
"Food Hygiene and Toxicology in Ready-to-Eat Foods" is a solid reference for anyone in the food industry needing to understand the complex issues and mechanisms of biological control and chemical hazards to ensure food safety. infectious and non-infectious contaminants in raw, minimally processed, and prepared foods are covered in detail, as well as effective measures to avoid foodborne infections and intoxications. The book is written by an international team of experts presenting the most up-to-date research in the field, and provides current applications and guidance to enhance food safety in the food industry. Strategies and recommendations for each food category include, among others, how to avoid cross-contamination of pathogens, the proper uses of antimicrobial coatings and spray cleanings of fresh produce, and acrylamide reduction during processing. leafy vegetables, fruit juices, nuts, meat and dairy products are some of the ready-to-eat foods covered.Provides the latest on research and development in the field of food safety incorporating practical real life examples for microbiological risk assessment and reduction in the food industryIncludes specific aspects of potential contamination and the importance of various risks associated with ready-to-eat foodsDescribes potential harmful agents that may arise in foods during processing and packagingPresents information on psychrotropic pathogens and food poisoning strains, effect of temperature, "Salmonella," "Listeria," "Escherichia coli," "Bacillus cereus," "Norovirus," parasites, fungal microbiota, enterotoxins, and more - Resumé vydavatel